Herder Publishers and the Second Vatican Council - O'Collins, Gerald (Theological studies, 2020)
This article examines the contribution made by the publishing house of Herder to the reception of the teaching and decisions of Vatican II (1962–1965). This input began with the five volumes of Commentary on the Documents of Vatican II (German original 1966–1968), edited by Herbert Vorgrimler and including contributions from twenty-one authors who had played roles in drafting the Council’s sixteen documents and could expound from the inside the authorial intentions (intentio auctoris) of these texts. The subsequent five volumes of the Herders Theologischer Kommentar (2004–2009), edited by Peter Hünermann, could also explore the post-Vatican II history of interpretation and implementation of the conciliar texts (the intentio textus) and the insights of readers with their different questions and expectations (the intentio legentis).